2018
DOI: 10.1242/jcs.217042
|View full text |Cite
|
Sign up to set email alerts
|

Perilipin-2 is critical for efficient lipoprotein and hepatitis C virus particle production

Abstract: In hepatocytes, PLIN2 is the major protein coating lipid droplets (LDs), an organelle the hepatitis C virus (HCV) hijacks for virion morphogenesis. We investigated the consequences of PLIN2 deficiency on LDs and on HCV infection. Knockdown of PLIN2 did not affect LD homeostasis, likely due to compensation by PLIN3, but severely impaired HCV particle production. PLIN2-knockdown cells had slightly larger LDs with altered protein composition, enhanced local lipase activity and higher β-oxidation capacity. Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…In agreement with this idea, the silencing of Rab18, a lipid droplet-associated cellular protein which binds to NS5A, reduces the association of other HCV replication complex components with LDs (Salloum et al, 2013). In addition, in a recent study, a defect in PLIN2/ADRP, the major LDs coat protein in hepatocytes, restricted the LD access for HCV core and NS5A proteins and reduced intracellular infectious HCV particle formation (Lassen et al, 2019).…”
Section: Lds-involvement In Flaviviridae Life Cyclementioning
confidence: 74%
“…In agreement with this idea, the silencing of Rab18, a lipid droplet-associated cellular protein which binds to NS5A, reduces the association of other HCV replication complex components with LDs (Salloum et al, 2013). In addition, in a recent study, a defect in PLIN2/ADRP, the major LDs coat protein in hepatocytes, restricted the LD access for HCV core and NS5A proteins and reduced intracellular infectious HCV particle formation (Lassen et al, 2019).…”
Section: Lds-involvement In Flaviviridae Life Cyclementioning
confidence: 74%
“…Diacylglycerol acyltransferase-1 localizes NS5A to LDs and promotes NS5A and core interaction (14). Perilipin-2 expression is required for trafficking of core and NS5A to LDs and for the formation of HCV particles (15). We also showed that overexpression of PACSIN2 promotes NS5A and core interaction, which facilitates HCV particle assembly (16).…”
mentioning
confidence: 69%
“…The capsid also showed extensive localization on LDs, and quantitation of LD number showed a significant decrease in infected cells. However, studies with DENV and HCV have shown that LDs increase during infection [21,53]. It is possible that lipid metabolism is differentially regulated by JEV, which is primarily a neurotropic virus.…”
Section: Discussionmentioning
confidence: 99%